PENGARUH MODUL TERMOKIMIA BERBASIS STEM TERHADAP HASIL BELAJAR DAN MOTIVASI BELAJAR MAHASISWA PADA MATA KULIAH KAPITA SELEKTA KIMIA - Susilawati Amdayani; Makharany Dalimunthe; Haqqi Annazili Nasution (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
This research is motivated by the low ability of students in developing critical thinking skills and problem solving and the lack of student motivation to develop science and link chemistry with other science. This research is a quantitative research. This study aims to determine the effectiveness of STEM-based modules on learning outcomes and student motivation. The type of research used is a quasi-experimental design using a non-equivalent control group pretest-posttest design. The data collection method used was a multiple choice test to measure learning outcomes and a questionnaire to analyze learning motivation. The results showed that the use of STEM-based modules had an effect on student learning outcomes and learning motivation in selected subjects.